Tasawuf Qurani Jawi Ki Ageng Suryomentaram Studi Kawruh Jiwa - Abdul Muid Nawawi; Mulawarman Hannase; Abdullah Safei (Mumtaz: Jurnal Studi Al-Quran dan Keislaman, 2019)
Kawruh jiwa Ki Ageng Suryomentaram focuses on human feeling in spiritual matters to live a happy life and not just physical aspects. The spiritual aspect must grow on the sense of self itself, while the physical aspects will arise after the growth of the spiritual aspects that are carried out. The spiritual aspect must be in line and side by side with the physical aspect to produce a complete sense of human self. Ki Ageng Suryomentaram asserted that he invited us as Indonesian people to feel the feelings of life, examine every taste, and achieve the true meaning of happiness. Happiness is not out there, but inside yourself. Happiness is free, does not depend on time, place and circumstances. This study tries to invite all of us to be able to feel the happiness that is in us so that it reaches a complete human being with essential happiness given by the Creator, Allah SWT.